KREATIVITAS DAN PSYCHOLOGICAL CAPITAL PENGUSAHA BATU TEMPLEK DI KABUPATEN PURWAKARTA - Hasemi Fauzi Ma’mun; Dedeng Abdul Gani Amruloh; amna mawardi (Eqien - Jurnal Ekonomi dan Bisnis, 2019)
The purpose of this study is to determine the effect of creativity on the performance of SMEs. Population in this research is all of micro enterprise in templek stone industry in Purwakarta, number of sample used in this research is 21 micro enterprise, all member of population is used as sample. Primary data obtained through the distribution of questionnaires to the respondents ie owners or managers of SMEs, while secondary data obtained from BPS and other relevant agencies related to research, data analysis methods used in this study is multiple linear regression with the help of the program IBM SPSS version 23 . Based on the results of research and testing has been done show that partially creativity significantly influence the performance of SMEs templek stone, furthermore, the results of research and testing of psychological capital variable is known to have a partial influence not significant to performance, simultaneously or creativity and psychological capital have a positive and significant effect on the performance of Batu Templek micro enterprise in Purwakarta.